The Influence Of Price And Physical Evidence On Purchase Decisions On Shopee E-Commerce In The City Of Bengkulu - Husnul Nugroho; M Rahman Febliansa; Dennis Rydarto (Universitas Dehasen Bengkulu, 2026)
This research is important to understand how much influence Price and Physical Evidence together in forming online consumer Purchasing Decisions in Bengkulu City This research aims to examine the influence of price and physical evidence on purchasing decisions on Shopee e-commerce in Bengkulu City. The focus of this research is to find out whether price and physical evidence influence purchasing decisions on Shopee e-commerce in Bengkulu City. The approach used is a quantitative approach with primary data. The sample in this study was the people of Bengkulu City, namely 130 people. The results of the linear regression analysis are Equation Y = 1.909 + 0.470 X1 + 0.459 X2 + e, this describes a positive regression direction, meaning that the price variable, physical evidence, has a positive influence on purchasing decisions on Shopee e-commerce in Bengkulu City. From the results of calculations using SPSS 25, it can be seen that the coefficient of determination R square is 0.758. This means that the value of Price (X1) and physical evidence (X2) influences the purchasing decision (Y) by 75.8% while the remaining 24.2% is influenced by other variables not examined in this study. The results of the t-test at a significance level <0.05 explain that partially Price (X1) and physical evidence (X2) have a significant influence on purchasing decisions on Shopee e-commerce in Bengkulu city. If the f test result is less than 0.000, then the variables Price (X1) and physical evidence (X2) have a significant influence on purchasing decisions (Y) on Shopee e-commerce in Bengkulu city.